Dynamics of Multidimensional Interaction: The Beijing Upheaval of 1989 Revisited. Issue 2 (1st December 2019) - Chen, Rilly; Yan, Fei
Abstract : This article provides a multidimensional approach to understanding the interactional dynamics of political contention. By reexamining the highly influential case of the Beijing student movement in 1989 with newly published memoirs from top party leaders and central student figures of the movement, we show more clearly that the escalating conflict between the government and protesters and their nuanced interplay grew, developed, and took on its own identity as the process evolved. It was the increasingly boisterous divisions within both the Communist Party and the student body itself, coupled with their close interactional relationship and interdependence, that resulted in a violent outcome that neither party had envisaged or intended. This finding suggests that multidimensional interactions may have triggered causal processes that escalated both the scale and the influence of the mobilization.